Emergence of religion in human evolution - Rappaport, Margaret Boone, author.
1 online resource.
Keywords: "This book uses a multidisciplinary approach to describe millions of years of biological innovations that eventually give rise to the modern trait and its varied expression in humanity's many religions. Religious capacity is a highly elaborate, neurocognitive human trait that has a solid evolutionary foundation. The authors present a scientific model and a central thesis that the brain organs, networks, and capacities that allowed humans to survive physically also gave our species the ability to create theologies, find sustenance in religious practice, and use religion to support the social group. Yet, the trait of religious capacity remains non-obligatory, like reading and mathematics. The individual can choose not to use it. The approach relies on research findings in nine disciplines, including the work of countless neuroscientists, paleoneurologists, archaeologists, cognitive scientists, and psychologists. This is a cutting-edge examination of the evolutionary origins of humanity's interaction with the supernatural. It will be of keen interest to academics working in Religious Studies, Neuroscience, Cognitive Science, Anthropology, Evolutionary Biology, and Psychology"--